ADVANTAGES OF THE MONTESSORY METHOD ON ISLAMIC RELIGIOUS LEARNING FOR STUDENTS AT BRAINY BUNCH INTERNATIONAL ISLAMIC MONTESSORI SCHOOL MALAYSIA - Adilatul Fauziyah; M Nurul Ikhsan Saleh (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
The learning process in schools for students basically should be in line with the nature (stages of development) of the students themselves. The Montessori method in the learning process focuses on students as experts in their actions and practice where educators only act as observers of student work and facilitators for students. In addition, the Montessori method has a specialty, namely how students have sensitivity skills to the environment. Researchers conducted this study with the aim of analyzing the advantages of applying the Montessori method in instilling the values of Islamic religious education in students at Brainy Bunch International Islamic Montessori School Malaysia. The research method used is field research with descriptive analysis. This field research was carried out by direct observation from class to class as well as direct interviews with teachers. This study found that the Montessori method was very good at instilling Islamic values because this method tries to follow the nature of students and can be seen directly from students' behavior while at home or at school. The learning process in schools for students basically should be in line with the nature (stages of development) of the students themselves. The Montessori method in the learning process focuses on students as experts in their actions and practice where educators only act as observers of student work and facilitators for students. In addition, the Montessori method has a specialty, namely how students have sensitivity skills to the environment. Researchers conducted this study with the aim of analyzing the advantages of applying the Montessori method in instilling the values of Islamic religious education in students at Brainy Bunch International Islamic Montessori School Malaysia. The research method used is field research with descriptive analysis. This field research was carried out by direct observation from class to class as well as direct interviews with teachers. This study found that the Montessori method was very good at instilling Islamic values because this method tries to follow the nature of students and can be seen directly from students' behavior while at home or at school.